The adventures of Tom Bombadil : and other verses from The red book - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; Garland, Roger (Boston : Houghton Mifflin Co., 1991)
Describes Tom's encounters with Goldberry, the River-woman's beautiful daughter; with Old Man Willow, who tries to trap Tom inside his trunk; with the Badger-folk; and with the ghostly Barrow-wight, who dwells in the ancient mound on the hilltop.
Reprint. Originally published: Great Britain : Unwin Hyman Ltd., 1990.